Carrier suppression locked loop mechanism for UHF RFID readers - Villame, Deogracias P. (2010)
The receiver of a UHF RFID reader is exposed to strong carrier leakage signals due to antenna reflections and limited isolation of circulators and directional couplers. This strong interference limits the performance of the reader as the active components in the receiver become saturated. In this paper, an improvement on the front-end architecture of UHF RFID readers is presented to address this problem. An automatically-adjusted canceling signal is combined with the received signal to suppress the strong carrier leakage. The experiment results show that the constructed prototype can achieve high isolation and that the canceling signal can be routinely configured even during reader operations.
"April 2010."
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Radio frequency identification systems; Radio frequency modulation -- Transmitters and transmission; Frequency modulation detectors; Shortwave radio -- Antennas